2012
DOI: 10.1038/ejcn.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for augmented oxidative stress in the subjects with type 1 diabetes and their siblings: a possible preventive role for antioxidants

Abstract: BACKGROUND/OBJECTIVES: Oxidative stress (OS) is thought to be involved in both development of type 1 diabetes (T1D) and its further complications. In this study, certain biomarkers of OS were compared among the subjects with T1D, their non-diabetic siblings and unrelated healthy controls. SUBJECTS/METHODS: Known cases of T1D from both sexes aged 5-25 years were enrolled in a case-control study (n 1 ¼ 60). There were two control groups; non-diabetic siblings (n 2 ¼ 60) and unrelated apparently healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Moreover, beta cell viability is reduced after oxidative stress in H 2 O 2 or NO treated human islets (93). Consistent with these observations, serum levels of GPx and SOD are reduced in patients with T1D compared to healthy subjects (94). Thus, antioxidants may possess anti-diabetic potential in NOD murine model (95, 96) supporting this therapeutic strategy in patients with T1D (97, 98).…”
Section: Beta Cell Stresses: Source and Consequencementioning
confidence: 71%
“…Moreover, beta cell viability is reduced after oxidative stress in H 2 O 2 or NO treated human islets (93). Consistent with these observations, serum levels of GPx and SOD are reduced in patients with T1D compared to healthy subjects (94). Thus, antioxidants may possess anti-diabetic potential in NOD murine model (95, 96) supporting this therapeutic strategy in patients with T1D (97, 98).…”
Section: Beta Cell Stresses: Source and Consequencementioning
confidence: 71%
“…Treatment of nonobese diabetic (NOD) mice with glycolysis inhibitors resulted in delayed T1D onset and protected b-cell mass (24). In addition, as part of the OXPHOS program, the movement of electrons generates a substantial amount of reactive oxygen species (ROS) (25). The role of ROS in controlling the differentiation of T cells by modulating metabolism has recently been described (21,(25)(26)(27)(28)(29)(30).…”
Section: Metabolic Reprogramming Of T Cells In T1dmentioning
confidence: 99%
“…In addition, as part of the OXPHOS program, the movement of electrons generates a substantial amount of reactive oxygen species (ROS) (25). The role of ROS in controlling the differentiation of T cells by modulating metabolism has recently been described (21,(25)(26)(27)(28)(29)(30). Investigators have shown that ROS can act as signaling molecules involved in the process of T cell activation, proliferation, and function (26).…”
Section: Metabolic Reprogramming Of T Cells In T1dmentioning
confidence: 99%
“…A complex interplay between genetic and environmental factors leads to the autoimmune attack of the ␤ cells, and recent studies suggest that ␤ cell dysfunction may contribute to neoantigen formation, which instigates autoimmunity (2)(3)(4). Oxidative stress resulting from an imbalance in favor of oxidants over antioxidants has been suggested as a primary cause of ␤ cell dysfunction in T1D (5)(6)(7). Because of their role in the production and release of insulin, ␤ cells generate endogenous reactive species such as hydrogen peroxide, hydroxyl radicals, and peroxynitrites.…”
mentioning
confidence: 99%